2020
DOI: 10.1177/1524839919879928
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Reach Equity of Policies Restricting Flavored Tobacco Product Sales in the United States

Abstract: In 2009, flavored cigarettes (except menthol) were banned in the United States, but other flavored tobacco products (FTPs) were allowed. Women, populations of color, youth, sexual minority, and low-socioeconomic status populations disproportionately use FTPs. Localities have passed sales restrictions on FTPs that may reduce disparities if vulnerable populations are reached. This study assessed the extent to which FTP restrictions reached these subgroups ("reach equity"). We identified 189 U.S. jurisdictions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…This additional insight is particularly relevant for regions such as the South and Midwest, where rates of smoking and using menthol cigarettes are higher than in regions such as the West, 1,37 and an opportunity exists to advance tobacco control initiatives, including restrictions on menthol cigarettes sales. 38,39 Findings from this research can provide updated evidence to federal and local policy makers and advocates seeking to reduce tobacco use.…”
mentioning
confidence: 98%
“…This additional insight is particularly relevant for regions such as the South and Midwest, where rates of smoking and using menthol cigarettes are higher than in regions such as the West, 1,37 and an opportunity exists to advance tobacco control initiatives, including restrictions on menthol cigarettes sales. 38,39 Findings from this research can provide updated evidence to federal and local policy makers and advocates seeking to reduce tobacco use.…”
mentioning
confidence: 98%
“…According to the Risk Perception Attitude framework, behavior change cannot occur unless risk perceptions are corrected and efficacy is increased, so messaging should also use evidence-based strategies to increase efficacy in order to avoid menthol cigarettes (Rimal & Real, 2003). In addition, recent efforts by localities in the United States to ban the sales of menthol cigarettes in their jurisdiction can help to reduce tobacco use among these vulnerable groups who are most at risk of menthol use (Innocent, 2018; Rose et al, 2020). Modeling studies indicate that banning menthol in 2011 would have saved over half a million lives by 2050, with 37% of those among Blacks (Levy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings highlight the potential equity effect of passing any flavour policy, regardless of retailer-based exemption and informs other studies investigating flavour policies within marginalised communities disproportionately impacted by FTP use. 27 28 Stakeholders and policy-makers should incorporate an equity lens when considering a retailer-based exemption policy to ensure that FTP availability decreases equally in low-income populations and communities of colour.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that FTP policies equitably reach most racial/ethnic minority populations and individuals with lower socioeconomic status. 27 28 As recent federal policy and continued action at the state and local-level unfolds, there is a need to estimate the magnitude of effect that comprehensive bans could have on reducing access to FTPs nationwide. In addition, it is important to understand the extent to which the impact may be lessened by including retailer exemptions and the extent to which such exemptions may disproportionately impact vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%